DESAIN IMPLEMENTASI DATA WAREHOUSE DATA PENGGUNA NARKOBA BADAN NARKOTIKA NASIONAL PROVINSI BALI - Riskiyanti, Zuraida Malini Cantika Riskiyanti (Prodi Sistem Informasi FST Universitas Jambi, 2023)
Information Technology is growing rapidly from time to time. One example of the many developments in information technology is the implementation of a data warehouse. The data warehouse is a mutually reacting database that can be used for queries and analysis, subject-oriented, integrated, time-variant, unchanging that is used to help decision-makers. The Bali National Narcotics Agency Office needs to implement a data warehouse to manage data that will be reported regularly. Data warehouse implementation in the Office of the National Narcotics Agency of Bali Province requires supporting technologies such as Data Warehouse, OLTP (Online Transaction Processing), OLAP (Online Analytical Processing), ETL (Extract Transform Loading), Cloud Computing. The implementation of the data warehouse is expected to help employees, especially staff who manage data on drug users periodically, the Office of the National Narcotics Agency of Bali Province to maximize data processing accurately and on time.